COMMUNITY-BASED HEARING LOSS EDUCATION AND SUPPORT GROUPS FOR OLDER HISPANIC/LATINO ADULTS. (11th November 2018) - Marrone, N; Ingram, M; Coco, L; Piper, R; Colina, S; Carvajal, S
Abstract: Envisioning hearing health care from a community-based approach provides a new pathway for hearing loss identification, evaluation, and treatment. Hearing loss can have a significant impact on communication and quality of life for individuals as well as their family and communities. This presentation will highlight the development and implementation of a community-based hearing health education intervention. We will discuss the partnership between community health workers and audiologists that was formed to identify and serve individuals and families experiencing the consequences of hearing loss in an underserved rural community. Following identification of hearing loss, educational sessions emphasizing peer-support and communication training were used to provide participants with strategies for effective communication. Results suggest increased use of communication strategies, improved adaptations in social environments, and overcoming barriers in access to care. This presentation will provide recommendations for those serving older adults to enhance communication across the lifespan and promote healthy aging.